Transcatheter closure of congenital portosystemic shunts - A multicenter experience - Nageswara Rao Koneti; Shweta Bakhru; Mahimarangaiah Jayranganath; Mahesh Kappanayil; Prashant Bobhate; Lakshmivenkateshiah Srinivas; Snehal Kulkarni; Usha Mandikal Kodandarama Sastry; Raman Krishna Kumar (Wolters Kluwer Medknow Publications, 2022)
Background: Congenital portosystemic shunts (CPSS) are rare and present variably with hepatic encephalopathy, pulmonary arteriovenous malformations (PAVMs), and pulmonary hypertension (PH). Objective: The objective of the study was to see the feasibility of transcatheter closure of CPSS and their outcome. Materials and Methods: We analyzed the data of 24 patients of CPSS who underwent transcatheter closure from five institutions (March 2013 to April 2019). Baseline evaluation included echocardiography with bubble contrast study, ultrasound examination of the abdomen, computed tomography angiogram, and cardiac catheterization with test balloon occlusion of the CPSS. The evaluation showed cyanosis due to PAVM in 12, PH in 8, and respiratory distress in 2. Two had both cyanosis and PH. Criteria for eligibility for complete catheter closure of CPSS included demonstration of intrahepatic portal vein (PV) radicals together with a PV pressure of ≤18 mmHg on occlusion. Results: The median age and weight were 8 years (0.5-21) and 19.5 kg (4.2-73), respectively. Transcatheter closure was performed in 21 patients (22 procedures) using a variety of occlusive devices and stent-graft exclusion was done in one patient. Closure was not done in 3 in view of high portal venous pressures and hypoplastic PVs. During the follow-up (median: 42 months and range: 61 days-4.8 years), saturation normalized in 14 patients with PAVM. PH declined in all eight patients who underwent the procedure. Respiratory distress improved in two patients. Conclusions: Early and short-term follow-up results of catheter closure of CPSS appear promising. However, further, follow-up is needed to demonstrate long-term effectiveness.